In silico Evaluation and Neuroprotective Effect of Jasmonic Acid on Sleep Deprivation Induced Alzheimer’s in Zebrafish - Thamaraikani, Tamilanban; Anandan, Vijay B.; Karnam, Manasa; Vasanthan, Manimaran; Kichenamurthy, Gayathiri (Current Bioactive Compounds, 2023)
Background: Disturbances in the sleep cycle have been often associated with the depletion of oxidant enzymes and deposition of beta-amyloid plaques leading to neurodegeneration in Alzheimer's disease (AD). Healthy sleep time and sleep cycles were proven to clear the betaamyloid out of the brain and also promote the synthesis and functions of anti-oxidant enzymes. Objective: Jasmonic acid was evaluated to enhance the cognition and acetylcholine enzyme in the sleep deprivation-induced Alzheimer's by using the zebrafish model. Methods: The molecular properties, bioactivity score, and pharmacokinetic parameters of jasmonic acid were predicted using Molinspiration, SwissADME, and PreADMET tools. Jasmonic acid obeys Lipinski's rule and has significant bioavailability and blood-brain barrier penetration. The prediction of binding energy and interactions of jasmonic acid with six selected receptors was performed using AutoDock 4.2 software. It has significant binding affinity and interactions with different receptors which predict a multi-target potential using in-silico studies. In vivo neurobehavioral analysis of jasmonic acid was performed with zebrafish by using T-maze, Y-maze, and inhibitory avoidance apparatus and the results reveal Jasmonic acid produces more memory retention in zebrafish. In vitro assays of jasmonic acid on acetylcholinesterase enzyme level, glucose level, catalase activity, and lipid peroxidation activity were performed. Jasmonic acid shows cholinesterase inhibition, it acts as a good anti-oxidant and increases glucose metabolism on zebra fish brain homogenate using various assays. Jasmonic acid decreases neurodegeneration, and amyloid deposits in zebrafish brains using histopathological studies. Results: In silico molecular docking studies, in vitro assays, in vivo neurobehavioral analysis and histopathological studies reveal that jasmonic acid showed significant activity against sleep deprivation- induced AD in the zebrafish model. Conclusion: Hence, jasmonic acid will be carried out for further preclinical and clinical studies in order to prove the same for the management of Alzheimer's disease.
Keywords: autodock